Social Media: A Tool of Creation: Exploring the impact of social media on communication (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Social media is the collective of online communications channels dedicated to community-based input, interaction, content-sharing and collaboration.Websites and applications dedicated to forums micro blogging, social networking, social bookmarking, social citation, and wikis are among the different types of social media. We can’t afford to unleash our presence on social, it’s as essential as any other thing in your life.Here are some prominent examples of social media use for share and creation of necessary information.•Facebook is a popular free social networking website that allows registered users to create profiles, upload photos and video, send messages and keep in touch with friends, family and colleagues. According to statistics from the Nielsen Group, Internet users within the United States spend more time on Facebook than any other website.•Twitter is a free micro blogging service that allows registered members to broadcast short posts called tweets. Twitter members can broadcast tweets and follow other users' tweets by using multiple platforms and devices.•Google+ (pronounced Google plus) is Google's social networking project, designed to replicate the way people interact offline more closely than is the case in other social networking services. The project’s slogan is “Real-life sharing rethought for the web.”•Wikipedia is a free, open content online encyclopedia created through the collaborative effort of a community of users known as Wikipedia `ns. Anyone registered on the site can create an article for publication registration is not required to edit articles. Wikipedia was founded in January of 2001.•LinkedIn is a social networking site designed specifically for the business community. The goal of the site is to allow registered members to establish and document networks of people they know and trust professionally.•Reddit is a social news website and forum where stories are socially curated and promoted by site members. The site is composed of hundreds of sub-communities, known as sub reddits. Each sub reddit has a specific topic such as technology, politics or music. Reddit site members, also known as, redditors, submit content which is then voted upon by other members. The goal is to send well-regarded stories to the top of the site's main thread page.•Pinterest is a social citation website for sharing and categorizing images found online. Pinterest requires brief descriptions but the main focus of the site is visual. Clicking on an image will take you to the original source, so, for example, if you click on a picture of a pair of shoes, you might be taken to a site where you can purchase them. An image of blueberry pancakes might take you to the recipe a picture of a whimsical birdhouse might take you to the instructions.